Confronting and Reimagining the Orientation of International Graduate Students: A Collaborative Autoethnography Approach - Shokirova, Takhmina; Brunner, Lisa Ruth; Karki, Karun Kishor; Coustere, Capucine; Valizadeh, Negar (Journal of Teaching and Learning, 2022)
This paper uses lived experiences to critically examine the orientation of international graduate students at research-intensive Canadian universities. We, five co-authors, embody diverse ethnic, racial, sexual, religious, national, and gender identities, yet are all (or have been) international graduate students in Canada. Through collaborative autoethnography, we destabilize the notion of “orientation.” We argue that international student orientation should be understood as a fluid, ongoing process rather than one with rigid boundaries and timelines. Furthermore, orientation programming should more deeply consider the intersecting identities and positionalities of international students as multifaced individuals, as well as the implicit expectations of one-way “integration” into settler-colonial Canadian society. We suggest a different approach to orientation and offer a conceptual framework to guide future practice, highlighting the role universities play in not only supporting students academically but also in (im)migrant settlement.